Potential of Chitosan from Mangrove Snail Shells (Telescopium sp.) in Body Scrub Formulation - Sihombing, Kevin Andreas; Hasan, Bustari; Sidauruk, Santhy Wisuda (Aquatic Life Sciences, 2025)
Mangrove snails (Telescopium sp.) are a potential source of chitin-rich shells, which can be converted into chitosan with antimicrobial, humectant, and natural thickening properties suitable for cosmetic applications. This study aimed to evaluate the effect of varying chitosan concentrations on the quality and shelf life of body scrubs and to identify the optimal concentration for formulation. An experimental approach was employed, assessing chitosan characteristics (yield, moisture content, ash content, nitrogen content, and degree of deacetylation) and product quality parameters (homogeneity, humectant capacity, viscosity, adhesiveness, spreadability, pH, total bacterial count, and total fungal count) over a 30-day storage period. Chitosan derived from mangrove snail shells showed a yield of 9.91%, with 6.10% moisture, 6.34% ash, 6.57% nitrogen, and 67% degree of deacetylation. The 2% chitosan formulation yielded the best results, with favorable humectant capacity (94.75%), viscosity (3746.05 cps), adhesiveness (6.12 s), spreadability (6.52 cm), pH (6.38), and low microbial counts (10³ CFU). Chitosan’s antimicrobial activity contributed to maintaining product quality and safety throughout the 30-day shelf life.